Comparison of Non-suicidal Self-Injury and Suicide Attempts in Relation to Anger Rumination - Kilicaslan, Asli Kazgan; Yildiz, Sevler; Kurt, Osman; Atmaca, Murad (Aves, 2022)
Background: Angry rumination (AR) defined as thinking about the causes and consequences of anger by focusing on the feelings and experiences of anger can trigger suicide attempts and non-suicidal self-injury. The purpose of this study was to compare subjects with non-suicidal self-injury and subjects with suicide attempts in relation to anger rumination and also to determine if there is a relationship between anger rumination with non-suicidal self-injury and suicide attempts, and if so, to determine the direction of this relationship. Methods: In this study, 42 subjects with suicide attempts and 42 subjects with non-suicidal self-injury were included. Sociodemographic Data Form, Beck Depression Inventory, and Anger Rumination Scale were applied to all participants, Suicide Behaviors Questionnaire to those with suicide attempts, and Inventory of Statements About Self-Injury to those with non-suicidal self-injury. Results: Those with non-suicidal self-injury group had significantly higher thoughts of revenge (P =.038), angry afterthoughts (P =.047), and a higher total score of Anger Rumination Scale (P =.025) than those with suicide attempts group. The Beck Depression Inventory scores of suicide attempts group were significantly higher than those of non-suicidal self-injury group (P =.001). A positive and significant correlation was found between Suicide Behaviors Questionnaire and Anger Rumination Scale-total score (r = 0.322, P =.037) and Beck Depression Inventory score (r = 0.440, P =.004). Conclusions: Individuals with non-suicidal self-injury have more anger rumination, angry afterthoughts, and revenge-related thoughts following anger experiences than individuals with suicide attempts. As the severity of suicidal behavior of individuals with suicide attempts increases, so does their anger rumination. Our study may shed light on a better understanding of non-suicidal self-injury and suicide attempts and even contribute to intervention programs for these behaviors.
Keywords: anger rumination; non-suicidal self-injury; rumination; suicide